Impact of delay in follow‐up due to COVID‐19 pandemic on skin cancer progression: a real‐life experience from an Italian hub hospital. (4th March 2021) - Valenti, Mario; Pavia, Giulia; Gargiulo, Luigi; Facheris, Paola; Nucca, Ombretta; Mancini, Luca; Sacrini, Francesco; Borroni, Riccardo G.; Narcisi, Alessandra; Costanzo, Antonio
Abstract: Background: The COVID‐19 pandemic required the setting of a national lockdown in Italy from March 9, 2020, until May 18, 2020; therefore, most of the non‐COVID‐19 activities were postponed. As a consequence, many follow‐up visits in patients with previously excised skin cancers were delayed. The aim of this retrospective real‐life case–control study is demonstrating that delay in follow‐up led to an increased incidence of advanced melanoma and keratinocyte cancers on the total of surgically excised skin cancers. Methods: The incidence of excised advanced melanoma and keratinocyte cancers in our dermato‐surgery division in the period May 18 to November 18, 2020, was compared to the same time span of 2019. All data were collected from the electronic database of our department. Odds ratio with 95% confidence interval was used to assess the risk of excised advanced skin cancers in 2020 compared to 2019. Results: From May to November 2019, we performed 265 surgical excisions, while during the pandemic in 2020, we completed 280 surgeries. The number of advanced skin cancers excised between May 18 and November 18, 2020, was significantly higher compared with the same period in 2019 (54 vs. 22, OR: 2.64; 95% CI: 1.56–4.47; P  = 0.0003). Significant differences were also observed regarding the number of surgically removed advanced BCCs (OR 2.15; 95% CI 1.14–4.07; P  = 0.0187) and advanced SCCs (OR 4.60; 95% CI 1.31–16.18; P  = 0.0175). Conclusion: These results confirm that delay in follow‐up and, consequently, postponed surgical excisions are related to an increased incidence of advanced skin tumors, resulting in poorer prognosis lifelong. Follow‐up visits should be carried on even during COVID‐19 pandemic, avoiding significant delays as much as possible.